Manajemen Pendidikan Kearifan Lokal Syekh Muhammad Arsyad Al Banjari Kalimantan Selatan Indonesia sebagai Sumber Kekayaan Pendidikan - Jarkawi Jarkawi (Jurnal Humaniora dan Ilmu Pendidikan, 2022)
Indonesia has a wealth of local wisdom full of values of justice, honesty and wisdom as well as education in building quality, competitive and characterized human resources as a source of educational wealth for now and the future. The local wisdom figures in their thoughts and actions are very rich to be used as role models and follow in their footsteps for everyone who wants a progress in education. Purpose: The aim of this research is to find out the Factual Conditions of Local Wisdom Education Management Figure Syekh Muhammad Arsyad Al Banjari. Methodology: The method used in this research is to use a qualitative approach through a realist ethnographic design. Results: The results of this study are that Education Management with the wisdom of local figure Syekh Muhammad Arsyad Al Banjari is intellectual property in managing education which can be used as a reference in managing education and learning as well as inspiration in thinking for managers of formal and non-formal educational institutions as well as informal approaches who are local leaders in education management as role models in creating quality and character human resources.